Infrared Absorption Spectroscopy of Albumin Binding with Amine-Containing Plasma Polymer Coatings on Nanoporous Diamond Surfaces - Kozak, Halyna; Artemenko, Anna; Ukraintsev, Egor; Choukourov, Andrei; Rezek, Bohuslav; Kromka, Alexander (Langmuir, 2019)
Nanocrystalline diamond (NCD) layers functionalized with amine-containing functional groups have generated considerable interest as biocompatible substrates for attachment of biomolecules and cells with a view to biosensor and tissue engineering applications. Here we prepare nanoporous diamond layers with the surfaces modified by hydrogen plasma, oxygen plasma, and conformal 7 nm amine-containing plasma polymer (PP). Immobilization of bovine serum albumin (BSA) molecules is characterized on such surfaces. Grazing angle reflectance infrared spectroscopy as well as X-ray photoelectron spectroscopy show that concentration of amine-containing bonds after BSA exposure depends on the type of NCD surface modification. AFM measurements reveal that BSA proteins are physisorbed on H- and O-terminated diamond surfaces in different thicknesses and morphology. When the diamond layers are coated with the amine-containing PP, BSA molecules assume similar thickness and morphology, and their adhesion is significantly increased on both types of the diamond surfaces.
Keywords: Cattle; povrchové vlastnosti; Animals; skot; Spectrophotometry, Infrared; Nanopores; nanopóry; sérový albumin hovězí; diamant; zvířata; Serum Albumin, Bovine; Surface Properties; plazmové plyny; Diamond; spektrofotometrie infračervená; Plasma Gases